2015
DOI: 10.1177/0300985814565133
|View full text |Cite
|
Sign up to set email alerts
|

Oral Papillomas Associated With Felis catus Papillomavirus Type 1 in 2 Domestic Cats

Abstract: Multiple small sessile raised lesions were detected on the ventral surface of the tongue in two 13-year-old domestic cats. The lesions were incidental in both cats. Lesions from both cats appeared histologically as well-demarcated foci of markedly thickened folded epithelium that formed keratin-filled shallow cuplike structures. Large keratinocytes that contained a swollen nucleus surrounded by a clear cytoplasmic halo (koilocytes) were common, suggesting a diagnosis of a papillomavirus-induced papillomas, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 10 publications
(24 reference statements)
3
47
0
Order By: Relevance
“…Therefore, if feline OSCCs are caused by a PV infection, FcaPV-1 and FcaPV-4 appear to be the most likely etiological agents. Recently it was found that FcaPV-1 is not amplified by the consensus PCR primers used in the three earlier studies (Munday et al, 2015). Therefore, it was hypothesized that the feline oral PVs could be a significant cause of feline OSCCs without having been previously detected.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, if feline OSCCs are caused by a PV infection, FcaPV-1 and FcaPV-4 appear to be the most likely etiological agents. Recently it was found that FcaPV-1 is not amplified by the consensus PCR primers used in the three earlier studies (Munday et al, 2015). Therefore, it was hypothesized that the feline oral PVs could be a significant cause of feline OSCCs without having been previously detected.…”
mentioning
confidence: 98%
“…Currently four different Felis catus PV (FcaPV) types are recognized to infect domestic cats. Of these, only FcaPV-1 and FcaPV-4 have been detected in the mouth (Dunowska et al, 2014;Munday et al, 2015). Therefore, if feline OSCCs are caused by a PV infection, FcaPV-1 and FcaPV-4 appear to be the most likely etiological agents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal RB expression results in an accumulation of p16CD-KN2A protein (p16), which can be detected using immunohistochemistry. While the presence of p16 has not previously been investigated in horse SCC lesions, recent studies of skin and oral samples revealed that p16 immunoreactivity is rarely present within feline-negative PV SCCs (Munday et al 2011b), while there was an intense cytoplasmic and nuclear immunoreactivity in oral Papillomas associated with Felis catus Papillomavirus Type 1 (Munday et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The negative stain for p16 may be due to the lack of specificity of the monoclonal antibody used (anti-human) against the horse p16 but previously similar antibodies were shown to be useful in cats, where the specificity of monoclonal anti-human p16 antibodies for feline p16 has been documented (Munday et al 2015). Unfortunately, all these considerations are speculative because Papillomaviral doi: 10.17221/8386-VETMED DNA PCR assays were not performed.…”
Section: Discussionmentioning
confidence: 99%